HIV/AIDS among youth in urban informal (slum) settlements in Kenya: What are the correlates of and motivations for HIV testing? - Zulu Eliya M; Crichton Joanna; Beguy Donatien; Kabiru Caroline W (BMC, 2011)
Abstract Background Although HIV counseling and testing (HCT) is widely considered an integral component of HIV prevention and treatment strategies, few studies have examined HCT behavior among youth in sub-Saharan Africa-a group at substantial risk for HIV infection. In this paper we examine: the correlates of HIV testing, including whether associations differ based on the context under which a person gets tested; and the motivations for getting (or not getting) an HIV test. Methods Drawing on data collected in 2007 from 4028 (51% male) youth (12-22 years) living in Korogocho and Viwandani slum settlements in Nairobi (Kenya), we explored the correlates of and motivations for HIV testing using the Health Belief Model (HBM) as a theoretical framework. Multinomial and binary logistic regression analyses were employed to examine correlates of HIV testing. Bivariate analyses were employed to assess reasons for or against testing. Results Nineteen percent of males and 35% of females had been tested. Among tested youth, 74% of males and 43% of females had requested for their most recent HIV test while 7% of males and 32% of females reported that they were required to take their most recent HIV test (i.e., the test was mandatory). About 60% of females who had ever had sex received an HIV test because they were pregnant. We found modest support for the HBM in explaining variation in testing behavior. In particular, we found that perceived risk for HIV infection may drive HIV testing among youth. For example, about half of youth who had ever had sex but had never been tested reported that they had not been tested because they were not at risk. Conclusions Targeted interventions to help young people correctly assess their level of risk and to increase awareness of the potential value of HIV testing may help enhance uptake of testing services. Given the relative success of Prevention of Mother-to-Child Transmission (PMTCT) services in increasing HIV testing rates among females, routine provider-initiated testing and counseling among all clients visiting medical facilities may provide an important avenue to increase HIV status awareness among the general population and especially among males.